2018
DOI: 10.1016/j.ijpsycho.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology, everyday behaviors, and autonomic activity in daily life: An ambulatory impedance cardiography study of depression, anxiety, and hypomanic traits

Abstract: Discrepancies regarding the link between autonomic nervous system (ANS) activity and psychopathology may be due in part to inconsistent measurement of non-psychological factors, including eating, drinking, activity, posture, and interacting with others. Rather than sources of noise, behaviors like being active and being with others may be the behavioral pathways that connect psychopathology symptoms to autonomic activity. The present study examined whether behaviors mediate the association of depression, anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 72 publications
0
37
0
2
Order By: Relevance
“…Future research should nevertheless aim to elucidate the circumstances under which elevated heart rates can be observed in socially anxious participants. Such examination might include methods of ambulatory assessment to examine heart rate changes across a variety of everyday situations in socially anxious participants ( Sperry, Kwapil, Eddington, & Silvia, 2018 ). Additionally, socially anxious participants in our study were not clinically diagnosed and altered gaze patterns might only become apparent in a clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should nevertheless aim to elucidate the circumstances under which elevated heart rates can be observed in socially anxious participants. Such examination might include methods of ambulatory assessment to examine heart rate changes across a variety of everyday situations in socially anxious participants ( Sperry, Kwapil, Eddington, & Silvia, 2018 ). Additionally, socially anxious participants in our study were not clinically diagnosed and altered gaze patterns might only become apparent in a clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Although anxiety disorders are also associated with alterations in reward processing, two studies have failed to find an association between anxiety status and resting or average ambulatory PEP (Fu, Gibson, Mendes, Schembri, & Huang, 2018;Schmitz, Krämer, Tuschen-Caffier, Heinrichs, & Blechert, 2011). Further, studies that have examined depressive and anxiety symptoms together among undergraduates (Sperry, Kwapil, Eddington, & Silvia, 2018) and disorders together among clinical samples (Licht, Penninx, & de Geus, 2012) have also failed to identify differences in ambulatory PEP (Licht et al, 2012;Sperry et al, 2018). Taken together, since alterations in reward sensitivity is not an integral component of anxiety, PEP may not capture SNS alterations in emotion processing associated with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, a physiological mechanism may underlie the relationship between anxiety and difficulty resisting food cravings. Much research on anxiety has suggested that increased anxiety is associated with autonomic nervous system dysfunction, particularly reduced parasympathetic nervous system activity and reduced heart rate variability (see Sperry et al, 2018 for a brief review), although these findings are not uniform. While some research has resulted in similar findings for depression, these findings have been more heterogeneous and might be more accurately attributed to comorbid anxiety rather than to the specific impact of depression ( Rottenberg, 2007 ).…”
Section: Discussionmentioning
confidence: 99%